What drives junior doctors to use clinical practice guidelines? A national cross-sectional survey of foundation doctors in England & Wales. Issue 1 (December 2015) - Manikam, Logan; Hoy, Andrew; Fosker, Hannah; Wong, Martin; Banerjee, Jay; Lakhanpaul, Monica; Knight, Alec; Littlejohns, Peter
Abstract Background Clinical practice guidelines (CPGs) aim to improve patient care, but their use remains variable. We explored attitudes that influence CPG use amongst newly qualified doctors. Methods A self-completed, anonymous questionnaire was sent to all Foundation Doctors in England and Wales between December 2012 and May 2013. We included questions designed to measure the 11 domains of the validated Theoretical Domains Framework (TDF). We correlated these responses to questions assessing current and future intention to use CPGs. Results A total of 13, 138 doctors were invited of which 1693 (13 %) responded. 1, 035 (62.5 %) reported regular CPG use with 575 (34.4 %) applying CPGs 2–3 times per week. A significant minority of 606 (36.6 %) declared an inability to critically appraise evidence. Despite efforts to design a questionnaire that captured the domains of the TDF, the domain scales created had low internal reliability. Using previously published studies and input from an expert statistical group, an alternative model was sought using exploratory factor analysis. Five alternative domains were identified. These were judged to represent: "confidence", "familiarity", "commitment and duty", "time" and "perceived benefits". Using regression analyses, the first three were noted as consistent predictors of both current and future intentions to use CPGs in decreasing strength order. Conclusions In this large survey of newly qualified doctors, "confidence",  "familiarity" and "commitment and duty" were identified as domains that influence use of CPGs in frontline practice. Additionally, a significant minority were not confident in critically appraising evidence. Our findings suggest a number of approaches that may be taken to improve junior doctors' commitment to CPGs through processes that increase their confidence and familiarity in using CPGs. Despite limitations of a self-reported survey and potential non-response bias, these findings are from a large representative sample and a review of existing implementation strategies may be warranted based on these findings.